2019
DOI: 10.4236/ojog.2019.95070
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Sperm Antibodies: Prevalence of Ig A and Ig G Positive Serology among Infertile Patients in Kisangani, Democratic Republic of Congo

Abstract: Introduction: Infertility in a couple is a stressful situation. Among the causes is the presence of antisperm antibodies that play a harmful role in reducing fertility and negatively influencing in vitro fertilization. The aim of this study is to determine their prevalence among infertile patients in Kisangani. Patients and methods: We conducted an analytical cross-sectional study in health facilities in the city of Kisangani. Of the 1379 patients who consulted for conception, 311 were tested for antisperm ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The results of this study are in agreement with those of Bosenge et al [24] in Kisangani, who reported that 67% of infertile couples had secondary infertility and 33% primary infertility. These ndings are consistent with those from other Sub-Saharan African countries [16, 21,26,33]. The proportions of patients with primary and secondary infertility vary according to the aetiological particularities of each geographical region.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study are in agreement with those of Bosenge et al [24] in Kisangani, who reported that 67% of infertile couples had secondary infertility and 33% primary infertility. These ndings are consistent with those from other Sub-Saharan African countries [16, 21,26,33]. The proportions of patients with primary and secondary infertility vary according to the aetiological particularities of each geographical region.…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of pelvic in ammatory disease (PID) among women with secondary infertility in our study and in other sub-Saharan environments is mainly due to the high incidence of sexually transmitted infections (STIs), unsafe abortions and complications of childbirth, among other factors. PID can lead to infertility in several ways, including the production of antisperm antibodies, tubal obstruction and other complications [25,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations